A Novel flaB Gene-Based Profiling Approach for the Rapid and Accurate Detection of Borreliella and Borrelia Species in Ticks - Abigail Dorothea Taylor; Artur Trzebny; Małgorzata Łośko; Jerzy Franciszek Michalik; Miroslawa Dabert (Pathogens)
The increasing incidence of tick-borne diseases in Europe necessitates the development of accurate and high-throughput molecular tools for detecting pathogens in tick populations. In this study, we present a novel flaB gene-based profiling method for the detection and identification of Borrelia and Borreliella species in Ixodes ricinus ticks, combining newly designed primers with next-generation sequencing (NGS). The method was evaluated alongside conventional nested PCR targeting the flaB gene, as well as microbial profiling based on the V4 region of the rrs gene, using tick DNA extracted from 1088 specimens pooled into 94 samples. Our results demonstrate that the flaB gene-based profiling approach was the highest-performing out of the three methods, detecting Borreliaceae DNA in 83 DNA pools, compared to 58 and 56 pools using nested PCR and V4 rrs profiling, respectively. A total of 23 distinct flaB sequence variants were identified, corresponding to five Borreliaceae species: Borreliella afzelii, Bl. garinii, Bl. valaisiana, Bl. burgdorferi, and Borrelia miyamotoi. Additionally, the method enabled putative strain-level discrimination within species. Our results highlight the value of flaB gene-based profiling as a robust tool for ecological and epidemiological studies of Borreliaceae diversity in ticks.